Emergency Department Presentations and Youth Suicide: A Case-Control Study. (February 2019) - Rhodes, Anne E.; Sinyor, Mark; Boyle, Michael H.; Bridge, Jeffrey A.; Katz, Laurence Y.; Bethell, Jennifer; Newton, Amanda S.; Cheung, Amy; Bennett, Kathryn; Links, Paul S.; Tonmyr, Lil; Skinner, Robin
Objective: We estimate associations between emergency department (ED) diagnoses and suicide among youth to guide ED care. Method: This ED-based case-control study used data from the Office of the Chief Coroner and all EDs in Ontario, Canada. Cases ( n = 697 males and n = 327 females) were aged 10 to 25 years who died by suicide in Ontario between April 2003 and March 2014, with an ED contact in the year before their death. Same-aged ED-based controls were selected during this time frame. Crude and adjusted odds ratios (aORs) and 95% confidence intervals were calculated. Results: Among youth diagnosed with a mental health problem at their most recent ED contact (41.9% cases, 5% controls), suicide was elevated among nonfatal self-inflicted: 'other' injuries, including hanging, strangulation, and suffocation in both sexes (aORs > 14); cut/pierce injuries in males (aOR > 5); poisonings in both sexes (aORs > 2.2); and mood and psychotic disorders in males (aORs > 1.7). Among those remaining, 'undetermined' injuries and poisonings in both sexes (aORs > 5), 'unintentional' poisonings in males (aOR = 2.1), and assault in both sexes (aORs > 1.8) were significant. At least half of cases had ED contact within 106 days. Conclusions: The results highlight the need for timely identification and treatment of mental health problems. Among those with an identified mental health problem, important targets for suicide prevention efforts are youth with self-harm and males with mood and psychotic disorders. Among others, youth with unintentional poisonings, undetermined events, and assaults should raise concern.